Exploring Teachers’ Interactive Strategies for Teaching Speaking to Low-Level EFL Learners: A Case Study at an English Course - Iga Rahman; Syarifuddin Dollah; Muhammad Tahir (International Journal of Language, Education, and Literature, 2026)
This study aimed to explore the interactive strategies used by teachers in teaching speaking skills to low-level EFL learners, as these learners often experience difficulties in actively participating in classroom speaking activities. Employing a qualitative case study design, the study involved three English teachers teaching speaking classes at a private English course. Data were collected through classroom observations and semi-structured interviews and were analyzed using thematic analysis. The findings revealed that teachers implemented various interactive strategies to support learners’ speaking development, including daily expression memorization, small talk, scaffolding techniques (questioning, visual support, repetition, and feedback), games, pair work, task-based language learning, and affective interaction such as humor, motivation, and verbal appreciation. These strategies encouraged active participation, reduced learners’ anxiety, and provided meaningful opportunities for speaking practice. The study concludes that interactive teaching strategies play an important role in facilitating speaking instruction for low-level EFL learners, particularly in non-formal education contexts where learners require intensive support and engagement.